Intraoperative discomfort associated with the use of a rotary or reciprocating system: a prospective randomized clinical - Aline Cristine Gomes; Adriana Jesus Soares; Alexandre Augusto Zaia; Erick M Souza; Emmanuel João Nogueira Leal Silva (Korean Academy of Conservative Dentistry, 2017)
Objectives The aim of this randomized, controlled, prospective clinical study was to evaluate patients' intraoperative discomfort during root canal preparations in which either multi-file rotary (Mtwo) or single-file reciprocating (Reciproc) systems were used. Materials and Methods Fifty-five adult patients, aged between 25 and 69 years old, with irreversible pulpitis or pulp necrosis participated in this study. Either the mesiobuccal or the distobuccal canals for maxillary molars and either the mesiobuccal or the mesiolingual canals for mandibular molars were randomly chosen to be instrumented with Mtwo multi-file rotary or Reciproc single-file reciprocating systems. Immediately after each canal instrumentation under anesthesia, patient discomfort was assessed using a 1 - 10 visual analog scale (VAS), ranging from 'least possible discomfort' (1) to 'greatest possible discomfort' (10). The Wilcoxon signed-rank test was used to determine significant differences at p< 0.05. Results Little intraoperative discomfort was found in all cases. No statistically significant differences in intraoperative discomfort between the 2 systems were found (p = 0.660). Conclusions Root canal preparation with multi-file rotary or single-file reciprocating systems had similar and minimal effects on patients' intraoperative discomfort.